2011
DOI: 10.1590/s1806-66902011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de girassol sob diferentes lâminas de irrigação no Vale do Curu, CE

Abstract: Resumo - Palavras-chave -Helianthus annus. Déficit hídrico. Características agronômicas. Genótipos.Abstract -With the objective to value the influence of six levels of irrigation in the agricultural performance of two cultivars of sunflower, (Catissol 01 e Embrapa 122 V-2000), was made an experiment at the Experimental Farm, Valley of Curu River,county of Pentecoste, CE. The experimental design adopted was randomized blocks with divided plots, with four replicates. The effect of six levels of irrigation based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
2
26

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 9 publications
6
20
2
26
Order By: Relevance
“…The greatest average mass of a thousand achenes (M1000A) on irrigated sunflower with groundwater well were obtained with treatment D4. As for irrigation with sewage M1000A major averages were obtained with depth D3 corroborating with research by SILVA et al (2011) that also observed significant effects on the M1000A due different irrigation depths.…”
Section: Bulk Of Thousand Achenessupporting
confidence: 87%
“…The greatest average mass of a thousand achenes (M1000A) on irrigated sunflower with groundwater well were obtained with treatment D4. As for irrigation with sewage M1000A major averages were obtained with depth D3 corroborating with research by SILVA et al (2011) that also observed significant effects on the M1000A due different irrigation depths.…”
Section: Bulk Of Thousand Achenessupporting
confidence: 87%
“…Silva et al (2011) obtiverem produtividade média de 4.085 kg ha -1 com aplicação diária de lâmina de irrigação, correspondente a 150% da evapotranspiração do tanque classe A.…”
Section: Methodsunclassified
“…Apesar do girassol ser tipicamente cultivado em safrinha (Castro & Oliveira, 2005;Silva et al, 2007) e apontado como tolerante à deficiência hídrica (Castro & Farias, 2005;Toureiro et al, 2007), esta espécie responde positivamente à irrigação (Silva et al, 2009;Silva et al, 2011 …”
Section: Methodsunclassified
“…Esses resultados foram inferiores aos encontrados por Silva et al (2011), trabalhando com duas cultivares de girassol, onde foram verificados teores de 45% (Embrapa 122 V-2000) e 43% (Catissol 01). Pivetta et al (2012), avaliando seis híbridos de girassol, observaram que o híbrido com menor teor de óleo apresentou 35%.…”
Section: Figura 1 Efeito Das Lâminas De Irrigação Na Altura Das Planunclassified
“…Dentre as variáveis avaliadas, a massa de mil aquênios (VIANA et al, 2012), produtividade e teor de óleo (SILVA et al, 2007), diâmetro do caule e altura das plantas (SILVA et al, 2007; tem sido comumente utilizados na avaliação do cultivo de girassol. Silva et al (2011) definiram lâminas que proporcionaram maiores produção de aquênios e teores de óleo em diferentes variedades de girassol.…”
Section: Introductionunclassified